Labor Mobility of the Karakachans in Bulgaria – Circumstances and Motivation - Димитров, Начо (Poznańskie Studia Slawistyczne, 2015)
The term migration is used to describe a type of human behavior with immediate social, cultural, economic and political consequences. The researched cross-border labor mobility of the Karakachans in Bulgaria in the post socialist period affects more than 90% from the Karakachan families in only a few years. This problem is pressing concerning the protectional Greek policy towards the Karakachan community from the beginning of the 1990s and the following mutual related migratory and identity-processes. Subjects of the present research are the Karakachans in Bulgaria, the Bulgarian people married to Karakachans and children from mixed marriages. The topics of the research include the various circumstances and factors for their labor mobility in Greece after 1989. The basic aim of this work is to explain the problem about the origin of researched labor mobility, which should answer the questions why it is possible and very probable. As a result, the social-economic, political and cultural circumstances which are important for the origin and the development of the labor mobility of the Karakachans in Bulgaria since 1989, are being depicted and investigated here.